Risky sexual behavior among rural female adolescents in Malaysia: a limited role of protective factors - Ahmadian, Maryam; Hamsan, Hanina Halimatusaadiah; Abdullah, Haslinda; Abu Samah, Asnarulkhadi; Md Noor, Amna (Canadian Center of Science and Education, 2014)
Purpose: This paper presents the findings of a cross-sectional survey on the risk and protective factors of premarital sexual behavior among rural female adolescents in Peninsular Malaysia. Methods: We investigated data on 770 female respondents aged 13-17 years in rural areas to identify predictive factors for premarital sexual intercourse. Data were analyzed using bivariate and multivariate regression. Specific socio-demographic factors, psychological and family domains, peer delinquency, and knowledge and attitudes about sexuality were considered in risky sexual behaviors in rural Malay girls. The effects of other covariates for premarital sexual intercourse were controlled by logistic regression model. Results: Of the 770 rural female students, about 3.2% of respondents reported experience of sexual intercourse in the past three months. Out of those sexually active girls, 36% were 17 years old and 20% stated having sexual intercourse with more than one partner, and 72% did not use contraception during the most recent sexual intercourse. Midnight activities, peer-sexual disorder, self-evaluation, and attitude toward sexual health were significant predictors of sexual intercourse in rural girls in Malaysia. Conclusion: The finding highlights the impact of psychological factors and peer group influences on the challenges of premarital sexual behavior among rural girls and the notion of school-based sexual health education for adolescents. This study triggers other researchers take into account a comprehensive view of protective factors operating in adolescents’ risky sexual behaviors in Asian culture seeing that family domain variables, unexpectedly, exerted no predicting influence on sexually active female teens in rural areas in Malaysia.